Body awareness, body image and corporality in Physical Education: A literature review - Pereira, Claudiney André Leite (Seven Editora, 2024)
Our objective with this study will be to reflect based on a literature review on how the concepts of body awareness, body image and corporeality are present in Physical Education. Although the view on the human body has been greatly expanded in recent decades, Physical Education professionals are still seen by society as responsible for the body’s performance, that is, those who have the ability, through exercises, to tone their muscles and to make bodies healthier, given this it is necessary to know the values of the consumer society present in these relationships. DOI:https://doi.org/10.56238/sevened2024.014-019